Astrochemistry and Astrobiology over the last 20 years - Yeghikyan, A. G.
A review of the achievements of astrochemistry and astrobiology over the past 20 years is given. Advances in astrochemistry in understanding the processes of emergence and survival high molecular weight chemical compounds are directly related to the conditions of prebiomolecules origin, like -amino acids and complex hydrocarbons. And if on the case of amino acids and hydrocarbons synthesis , the astrophysical picture seems quite clear, then on the case of the emergence of chiral amino acids, of which the proteins of living organisms are composed, there is no generally accepted point of view. Probably they occurred in certain photochemical transformations under the influence of circularly polarized radiation in the conditions of star formation regions of molecular clouds.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture